Reductive Rearrangement of a 1‐Phospha‐2‐azanorbornene. Issue 29 (3rd May 2021) - Wonneberger, Peter; König, Nils; Sárosi, Menyhárt B.; Hey‐Hawkins, Evamarie
Abstract: The reduction of the 1‐phospha‐2‐azanorbornene derivate endo ‐1 with lithium aluminium hydride leads to an unprecedented 1‐phosphabicyclo[3.2.1]octa‐2, 5‐diene, while a phospholide anion is formed with lithium. The latter can be protonated resulting in formation of an unusual 2 H ‐phosphole dimer. Furthermore, 3 H ‐phospholes, previously assumed to have no synthetic relevance as intermediates, were proposed to act as dienophile in the dimerisation of 3, 4‐dimethyl‐1‐phenylphosphole at elevated temperatures based on theoretical calculations. Abstract : 1‐Phospha‐2‐azanorbornenes (PAN) are shown to be suitable starting materials for novel bridged 7‐membered phosphorus heterocycles (using lithium aluminium hydride as reducing agent) or lithium phospholide (with elemental lithium as reducing agent). Artwork by Dr. Christoph Selg.